ANALISIS PENGARUH RASIO CAEL TERHADAP RETURN SAHAM PADA EMITEN PERBANKAN - Ellen Erlambang; Dedhy Sulistiawan (CALYPTRA, 2018)
Banks have an important role in the economy of a country so that banks become one of investment opportunity that is quite promising for investors. It is underlying this research on the influence of CAEL ratio to stock return of banks in Indonesia. CAEL ratio is a financial ratios that can describe financial soundness of banks. This research is a quantitative research. This study aims to test the positive relationship between CAR and LDR as well as negative relationship between BOPO and NPL on stock return of banks. Test of CAEL ratio using secondary data which obtained from Capital Market Reference Center and Indonesia Stock Exchange which accessed through www.idx.co.id. The testing technique is carried out with a combined period (2011-2016) as well as a partial period every year. From this research, the majority results obtained that there is no relationship between CAEL ratio to stock returns of banks in the combined or partial period (2011-2016).